Assessment of the USG detection of abdominal pathologies in HIV and Aids and its association with CD4 counts - An original research - Sai V Kyasa; Kesava M Achuta; Manoj K Gupta; Rajunaik Ajmeera; Neeraj Kancherla; Faziljot Singh (Wolters Kluwer Medknow Publications, 2023)
Introduction: In individuals with acquired immunodeficiency syndrome (HIV/AIDS), abdominal pathologies rank second in frequency only to pulmonary illnesses. An essential imaging method for assessing abdominal diseases is ultrasonography (USG). In this study, abdominal pathologies in HIV/AIDS patients were evaluated using USG, and their relationship to CD4 count was further examined. Materials and Techniques: 400 HIV+ subjects with aberrant abdominal USG participated in the current investigation. The subjects were assessed and graded as per the CD4 counts. Later the comparisons were drawn between the USG, and its relationship to CD4 count using SPSS 16.0 software, and all data were examined using appropriate statistical tools. Results: Men were over 60% of the 400 subjects. The average age of these subjects was 35.6 years; the range for this age group was 6 to 63 years. Spleen involvement was found on ultrasonographic examination in 45.1% of subjects, while liver and lymph node involvement was seen in 43.6% of subjects. Substantial correlations between CD4 counts and findings such as periportal & mesenteric lymphadenopathy, localized pancreatic lesion, splenic microabscess, splenomegaly, and hepatomegaly were found. One percent of individuals had lymphoma, which affected the retroperitoneal lymph nodes, pancreas, and liver. Conclusion: Present research demonstrates the significance of abdominal ultrasonographic examination in HIV+ patients. CD4 counts have a big impact on how an HIV/AIDS patient's differential diagnosis is determined. The interpretation of USG results in relation to CD4 levels may aid in accurate diagnosis.